ORIGEN DE LAS ESTRATEGIAS DISTRIBUTIVAS POR REDUPLICACIÓN EN ESPAÑOL Y PORTUGUÉS ANTIGUOS - Luis Silva Villar (European Scientific Journal, ESJ, 2015)
Our knowledge about the unusual history of the syntactic construction Reduplicación Numeral Distributiva (RND) in Medieval Latin, Old Spanish and Old Portuguese is very limited. A prefab example of RND is *E ovo […] en cada pared de amos los costados treinta varas de V V cobdos…; i.e., ‘[…] varas de V codos cada una’. Reduplicative numbers disambiguates collective and distributive semantic interpretations. This construction is documented throughout four centuries (10th C-13th C.) in western Spain and Portugal. Defining the nature of this structure and documenting its evolution are two major goals in this research.